A STUDY OF TEACHERS’ VERBAL INTERACTIONAL FEEDBACK STRATEGY IN TEACHING ENGLISH AT SECOND GRADE OF SMK NEGERI 2 BARRU - Fajriani, Reka; Syam, Ummi Khaerati; Muhsin, Muh Arief (JKIP (Jurnal Keguruan dan Ilmu Pendidikan), 2018)
The objective of this research were to find out the kinds of verbal feedback strategy and how the feedback strategies used by English teachers in providing interactional feedback at second grade of SMK Negeri 2 Barru.  The researcher used descriptive-qualitative method. The subject of this research were two English teachers at SMK Negeri 2 Barru who had been teaching in second grade. The data were collected by observing 2 times for each teacher by using observation, interview and documentation. To gather the data, two English teachers and their students who were studying English as a foreign language were observed while they were in a teaching learning process. Their interactions in the classroom were recorded, transcribed, and then analyzed to find out the kinds of verbal feedback used by the teacher during the interaction. Then the data were analyzed by using qualitative method. The findings of this research indicated that the English teachers at SMK Negeri 2 Barruused both positive and negative feedback in the teaching and learning process. In terms of positive feedback, the teacher mostly used repetition, followed by praise and affirmation. In terms of negative feedback, the teacher also used a variety of ways which include repetition as the most common feedback provision, followed by clarification request, elicitation, explicit correction, and prompting.